Fabrication and Mechanical Characterization of Stir Cast AA6063-Borosilicate-Fly Ash Hybrid Metal Matrix Composites - Jims John Wessley, G; Gaith Franklin, A; J. Vijay, S (International Journal of Engineering and Technology, 2018)
This paper presents the development and characterization of aluminium alloy 6063 based metal matrix composite with varying combinations of fly ash and Borosilicate reinforcements.Â  In the present work, the aluminium alloy 6063 (AA) is taken at a constant 84 vol% while the reinforcements Fly Ash (FA) and Borosilicate (B) are varied in the proportions of 2%, 4% 8%, 125 and 14%. Six samples were fabricated by stir casting and the mechanical properties were analyzed using tensile test, hardness test and wear test while the microstructure is analyzed by obtaining SEM and EDX images of the specimen. It is seen that both the reinforcements used in this study, increased the tensile and wear resistance of the alloy. The desirable mechanical and micro structural properties were found to be in the specimen with 84% AA, 14% FA and 2% B. The tensile strength of the aluminum alloy at this desirable combination is found to increase by 11.97%, ductility by 36.75% and the wear resistance by 62%.Â  This metal matrix composite of AA6063 with fly ash and Borosilicate reinforcements can be used in automobile, aerospace and structural applications where wear resistance and tensile properties are mainly required.